IMPLEMENTASI KEPERAWATAN KELUARGA DENGAN TEKNIK RELAKSASI OTOT PROGRESIF UNTUK MENGURANGI NYERI PADA PASIEN GASTRITIS - Aritonang, Richardo Hasudungan; Pangaribuan, Resmi; Khairani, Ade Irma (SINERGI : Jurnal Riset Ilmiah, 2025)
Gastritis is a digestive system health problem that has a fairly high prevalence in Indonesia, especially in the city of Medan with an incidence rate of 91.6%. Gastritis is characterized by inflammation of the gastric mucosa which causes complaints of epigastric pain, nausea, vomiting, and discomfort in the stomach. The pain experienced by ulcer patients is generally acute and can interfere with daily activities, so that treatment interventions are effective and easy to implement. One non-pharmacological effort that can be used to reduce pain is the Progressive Muscle Relaxation (PMR) technique. This technique aims to reduce muscle tension, improve circulation, reduce cortisol levels, and provide a feeling of relaxation for the patient. This research uses a case study method with subjects as ulcer patients in the Medan Deli Health Center working area. Death care is provided through the stages of assessment, determining a death diagnosis, intervention planning, implementation and evaluation. The focused intervention is providing routine progressive muscle relaxation techniques with family assistance as part of family care. Evaluation was carried out using a numerical pain scale before and after intervention. The results of the study showed a decrease in the pain scale from moderate category (scale 6) to mild (scale 2) after the patient carried out progressive muscle relaxation exercises for three consecutive days. In addition, patients also report increased comfort, reduced anxiety, and improved sleep quality. Family involvement in accompanying patients has been proven to increase compliance with the interventions provided. In conclusion, the progressive muscle relaxation technique is effective for reducing pain in gastritis patients and can be applied as an alternative non-pharmacological therapy in primary health care. This intervention is also useful in increasing family participation in home health care efforts.